Potential of Portuguese vine shoot wastes as natural resources of bioactive compounds - Moreira, Manuela M. (2018)
ince annually a high amount of wastes is produced in vine pruning, the aim of this study was to evaluate the potential of vine shoots from two Portuguese grape varieties (Touriga Nacional - TN and Tinta Roriz - TR) to be used as a natural source of phenolic compounds. To reach this goal, three techniques were explored, namely microwave-assisted extraction (MAE), subcritical water extraction (SWE) and conventional extraction (CE). The phenolic composition of the extracts, antioxidant and biological activities were evaluated by spectrophotometry and chromatography. MAE and SWE produced the highest concentrated extracts. TR vine shoot variety had the highest antioxidant activity and total phenolic (32.1 ± 0.9 mg gallic acid equivalents/g dry sample), as well as flavonoid content (18.7 ± 1.2 mg epicatechin equivalents/g dry sample). For the first time, the biological activity of the vine shoot extracts was tested. Results demonstrated that all of them had antimicrobial potential against different bacteria and yeasts, and the ability of inhibiting -amylase and acetylcholinesterase enzymes, with MAE TR extracts being the most efficient. HPLC analysis enabled the identification of different phenolic compounds, with gallic acid, catechin, myricetin and kaempferol-3-O-rutinoside being the main contributors to the phenolic composition. Portuguese vine shoot wastes could serve as easily accessible source of natural antioxidants for the food or pharmaceutical industries.